Developing a Dayak Folk Storybook as Supplementary Material for Teaching Narrative Text - Gabriella Lyonni; Ikhsanudin Ikhsanudin; Eka Fajar Rahmani (Universitas Muhammadiyah Kalimantan Timur, 2023)
This study aimed to develop a Dayak Folk Storybook that can be used as supplementary material to teach the narrative text. This research is Design and Development Research. The respondents of this research were year-8 students of SMP Pelita Harapan Pontianak. This research was done by conducting three phases of the ADDIE approach: Analyze, Design, and Develop. The researchers analyzed the needs focusing on identifying the materials and tasks that should be created based on the result of students’ questionnaires, teacher’s interviews, and syllabus reviews in the analysis phase. Then, the phase continued to design the materials, creating the draft of the materials and tasks. Finally, it was finalized in the development phase of the product. The result of this research is a supplementary folk storybook for learning narrative text, namely Collection of Kalimantan Dayaknese Legends for Learning English Reading. From the result of internal evaluation of the product, it was indicated that the product was appropriate and relevant with the teacher’s and students’ background, needs, and preferences. Therefore, the supplementary storybook is recommended to be used by teachers to teach narrative text to 8th Grade students of junior high school.